PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA SISWA KELAS IV-A UPT SD NEGERI LATSARI TUBAN - Masfiyatus Umaroh; Sri Cacik; Tri Eko Baktiono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve mathematics learning outcomes on plane geometry (bangun datar) material through the application of the Problem Based Learning (PBL) model among fourth-grade students (Class IV-A) at UPT SD Negeri Latsari, Tuban Regency. Prior to the intervention, most students’ scores were below the Learning Achievement Criterion (KKTP) of 75, reflecting a broader national pattern in which Indonesian students’ mathematics literacy remains low, as shown by the 2022 PISA results. This study employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, implemented in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 30 fourth-grade students. Data were collected through learning outcome tests administered at the pre-cycle, Cycle I, and Cycle II stages, then analyzed descriptively together with the Normalized Gain (N-Gain). Results showed that the average score increased consistently from 59.83 (pre-cycle) to 68.67 (Cycle I) and 72.00 (Cycle II), while classical mastery rose from 23.33% to 43.33% and 50.00% respectively, with an overall N-Gain of 0.303 (medium category). However, the 75% classical mastery target had not yet been achieved by the end of Cycle II. These findings indicate that PBL contributed positively to improving students’ mathematics learning outcomes on plane geometry material, although its effectiveness across cycles was not fully linear, suggesting the contextual nature of PBL’s impact and the need for further pedagogical reinforcement.